2017
DOI: 10.1038/s41467-017-00351-8
|View full text |Cite
|
Sign up to set email alerts
|

Formation pathways of mesoporous silica nanoparticles with dodecagonal tiling

Abstract: Considerable progress in the fabrication of quasicrystals demonstrates that they can be realized in a broad range of materials. However, the development of chemistries enabling direct experimental observation of early quasicrystal growth pathways remains challenging. Here, we report the synthesis of four surfactant-directed mesoporous silica nanoparticle structures, including dodecagonal quasicrystalline nanoparticles, as a function of micelle pore expander concentration or stirring rate. We demonstrate that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 38 publications
(63 reference statements)
1
54
0
Order By: Relevance
“…We recently demonstrated that increased size dispersion in surfactant micelle systems with added pore expander (i.e., oil phase) favors the formation of cage‐like mesoporous silica with nonuniform cage structures rationalizing the appearance of the clathrate IV structure at twice the ammonium hydroxide concentration (vide supra). [ 9 ] In order to increase the micelle size dispersion and further bias the system toward such structures, we mixed two surfactants of different chain lengths (C 16 TAB and C 8 TAB, see Experimental Section). In conjunction with a 1.5‐fold increase of the amount of ammonium hydroxide relative to single‐layer conditions to promote multilayer growth, this indeed resulted in superstructures showing exclusively the clathrate IV structure (Figure 3d−f).…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…We recently demonstrated that increased size dispersion in surfactant micelle systems with added pore expander (i.e., oil phase) favors the formation of cage‐like mesoporous silica with nonuniform cage structures rationalizing the appearance of the clathrate IV structure at twice the ammonium hydroxide concentration (vide supra). [ 9 ] In order to increase the micelle size dispersion and further bias the system toward such structures, we mixed two surfactants of different chain lengths (C 16 TAB and C 8 TAB, see Experimental Section). In conjunction with a 1.5‐fold increase of the amount of ammonium hydroxide relative to single‐layer conditions to promote multilayer growth, this indeed resulted in superstructures showing exclusively the clathrate IV structure (Figure 3d−f).…”
Section: Figurementioning
confidence: 99%
“…Since the early reports on directed silica self‐assembly, [ 1 ] these materials and their derivatives in the bulk, [ 2,3 ] as films, [ 4 ] and as nanoparticles [ 5,6 ] have been the subject of extensive research efforts. Benign synthesis conditions, often in aqueous solutions at room temperature, concomitant low toxicity and favorable biocompatibility, [ 7 ] continuous structure discovery, [ 8–10 ] as well as their application potential across different areas, e.g. in catalysis, [ 11 ] energy, [ 12 ] and nanomedicine, [ 6,13 ] maintain high academic and industrial interest levels.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(vi)Other authors speak of spatially localized grains. For example, in [56] such grains are fabricated by manipulating nanoparticles, e.g. by stirring.…”
Section: Appendix Terminologymentioning
confidence: 99%
“…By taking advantage of accessible quasicrystalline phases in somatter systems (surfactant micelles in particular), it is possible to template the formation of mesoporous silica with similar order. [44][45][46] These methods offer an accessible approach to porous quasicrystals, on the one hand enabling studies of the interactions of guest molecules with porous quasicrystalline hosts, on the other hand providing, perhaps, an alternative pathway towards quasicrystalline MOFs.…”
Section: Examples Of Aperiodic Structures In Mofs and Cpsmentioning
confidence: 99%